Revitalization of Fiqh Rules in the Reform of Modern Islamic Family Law - Samsul Arifin; Nurul Abrari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The purpose of marriage is to form a harmonious and happy family. However, the impact of globalization, technology, and diverse social life in society makes the goal of marriage difficult to achieve. Issues related to marriage require a solution, therefore, these Islamic jurisprudence principles serve as a guide in addressing marriage issues, resulting in a more responsive and adaptive renewal of Islamic family law. This study uses a qualitative approach with a literature study approach. Primary data sources are Ihya' Ulumiddin and Al-Faraidul Bahiyyah, and secondary data are from books and journals. Data collection techniques through literature reviews. The analysis process is carried out by separating relevant data, then analyzing it in the form of descriptive analysis, and drawing conclusions by linking the data on marriage issues to relevant Islamic jurisprudence principles. The results of the study show that there are three rules of Islamic jurisprudence that are relevant to marriage issues 1. Al-umuru bi maqasidiha (All actions depend on their purpose) This rule is used as the basis for a judge to decide the law on marriage confirmation. 2. Al Aslu fi asyya' al ibahah hatta yadulla al dalil ala tahrim (The origin of something is permissible, so there is evidence that prohibits it) This rule provides legal confirmation about the permissibility of doing something until there is an argument that prohibits it, in the context of marriage, namely the permissibility of doing walimatul usr according to his ability. 3. Addararu yuzalu (harm must be eliminated) This rule seeks to realize the purpose of the law, namely for the benefit by rejecting all damage, in the context of marriage, namely the existence of a marriage dispensation by a judge for those who have not met the formal and material requirements of marriage.